The Complete Poetical Works of Edgar Allan Poe : Including Essays on Poetry - Poe, Edgar Allan, 1809-1849; Ingram, John Henry, 1842-1916 (Salt Lake City, UT : Project Gutenberg, 2003)
"The Complete Poetical Works of Edgar Allan Poe" by Edgar Allan Poe is a comprehensive collection of the renowned poet's poems, likely compiled in the late 19th century. This edition, edited by John H. Ingram, includes both well-known poems and previously unpublished works. The book serves as a significant exploration of themes such as love, loss, and the macabre, capturing the essence of Poe's unique style and profound emotional depth. The opening of this collection features a preface by John H. Ingram, who outlines the uniqueness of this edition compared to earlier collections, emphasizing the inclusion of previously unprinted poems. It provides insights into Poe's life, shedding light on the misconceptions surrounding him and highlighting his struggles with personal tragedy and societal perception. Following the preface, the book begins with a rich selection of some of Poe's most famous works, including "The Raven" and "The Bells," infusing the early chapters with a haunting sense of melancholia and lyrical brilliance characteristic of Poe's poetry. (This is an automatically generated summary.)
Release date is 2003-11-01
Clytie Siddall, Charles Aldarondo, Keren Vergon and the Online Distributed Proofreading Team.
Keywords: Fantasy poetry, American